Blood Flow Mimicking Aneurysmal Wall Enhancement: A Diagnostic Pitfall of Vessel Wall MRI Using the Postcontrast 3D Turbo Spin-Echo MR Imaging Sequence - Kalsoum, E.; Chabernaud Negrier, A.; Tuilier, T.; Benaïssa, A.; Blanc, R.; Gallas, S.; Lefaucheur, J.-P.; Gaston, A.; Lopes, R.; Brugières, P.; Hodel, J. (American Journal of Neuroradiology, 2018)
SUMMARY: Our aim was to compare the detectability of aneurysmal wall enhancement in unruptured intracranial aneurysms between conventional and motion-sensitized driven equilibrium–prepared postcontrast 3D T1-weighted TSE sequences (sampling perfection with applicationoptimized contrasts by using different flip angle evolution, SPACE). Twenty-two patients with 30 unruptured intracranial aneurysms were scanned at 3T. Aneurysmal wall enhancement was more significantly detected using conventional compared with motion-sensitized driven equilibrium–prepared SPACE sequences (10/30 versus 2/30, P < .0001). Contrast-to-noise ratio measurements did not differ between conventional and motion-sensitized driven equilibrium–prepared sequences (P = .51). Flowing blood can mimic aneurysmal wall enhancement using conventional SPACE sequences with potential implications for patient care.AWEaneurysmal wall enhancementCNRcontrast-to-noise ratioMSDEmotion-sensitized driven equilibriumSPACEsampling perfection with application-optimized contrasts by using different flip angle evolutionUIAunruptured intracranial aneurysm